The Influence of Income, Islamic Financial Literacy, and Education on Well-Being through Financial Planning in Semarang - Sapta, Andriyan Eka; Samani; Nurhayati, Ida; Karyanti, Tutik Dwi; Wardana, Yanuar Wendy (Moneta : Journal of Economics and Finance, 2025)
The COVID-19 pandemic has caused economic instability in Indonesia, including in Semarang City, which has impacted the increasing poverty rate and difficulties in managing family finances. Under these conditions, financial literacy and financial planning have become crucial aspects that can help society face economic challenges. This research examines how income, Islamic financial literacy, and education influence community welfare through financial planning in the context of post-pandemic economic recovery. This research uses the Structural Equation Model (SEM) method based on variance with AMOS version 20 and involves 149 respondents selected using purposive sampling technique to analyze the relationships between income, Islamic financial literacy, education, financial planning, and welfare. The research results show that income does not have a significant influence on financial planning, while Islamic financial literacy and education have positive influences on financial planning. The study confirms that good financial planning contributes significantly to improving community welfare, with families having mature financial strategies being better able to achieve economic stability. These findings confirm the importance of improving Islamic financial literacy and broader access to education as main strategies to enhance community welfare. With better financial understanding, society can be wiser in managing income and developing more effective financial planning to achieve a more prosperous life, particularly in post-pandemic economic recovery contexts.